False and real, but avoidable, dichotomies - Ooms, Gorik; Flores, Walter; Mulumba, Moses; Sarker, Malabika; Van De Pas, Remco; Jahn, Albrecht (© 2017 Lancet Publishing Group, 2018)
This letter was published in The Lancet [© 2017 Lancet Publishing Group] and the definitive version is available at : http://doi.org/10.1016/S0140-6736(17)31445-9 The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S0140673617314459?via%3Dihub